REVITALISASI KEARIFAN LOKAL DALAM PENGELOLAAN LINGKUNGAN BERBASIS MASYARAKAT: PERAN PEREMPUAN BALI - Sandiasa, Gede (Universitas Panji Sakti, 2025)
Pacung Village in Tejakula District, Buleleng Regency, is one of Bali’s traditionalcommunities rich in living heritage and local wisdom. Amid social change and economicpressures, Balinese women play a pivotal role in sustaining cultural traditions, managingcommunity-based natural resources, and supporting household economies. Thiscommunity service project aims to identify the strategic role of women in culturalpreservation and explore how local traditions can be revitalized to strengthen communitybased creative economies. A participatory approach was applied through counselingsessions, focus group discussions (FGDs), and field observations involving women’sgroups (PKK), customary leaders, and village youth. The findings reveal that women act ascultural guardians, informal educators, household economic agents, and communitymobilizers. Local traditions such as crafts, traditional food processing, ritual plants, andcultural tourism hold great potential to be developed into new sources of income. Four keyempowerment strategies are recommended: thematic and regular training, cross-sectorcollaboration, the use of digital media for cultural documentation and promotion, and theestablishment of women-led cooperatives based on customary values. The revitalization oflocal wisdom through women’s leadership proves to be an effective pathway for achievingculturally rooted and sustainable village development.